CHARACTERISTICS AND PERFORMANCE OF SHALOT INDUSTRY IN INDONESIA - Andri, Kuntoro Boga; Wandschneider, Tiago; Kristedy, Teddy (Proceedings of the International Conference on Green Technology; Vol 6 No 1 (2015): Proceeding of International Conference on Green Technology, 2015)
In Indonesia, shallot ranks third amongst all vegetable crops in terms of cultivated area. Between 90,000 and 110,000 hectares are harvested every year and it is assumed that at least 100,000 rural households can be classified as shallot farm households. In addition, many men and women are working or hired in shallot farms and business at different stages along the product chain. This study was conducted to provide a description and analysis of the shallot Industry in Indonesia. Some information and analysis of the shallot chain are also provided due to the close links between shallot production and marketing. A review of existing studies, reports, and government statistics was carried out early on during the research and qualitative methods were employed for collection of primary data.  The fieldwork was carried out in January, February and December 2012 using Focus group discussions (FGD) with farmers and semi-structured interviews (SSI) with producers, other chain actors, and some knowledgeable observers in East Java and NTB. This study shows the productivity of shallot is still below the level of potential. Some production constraints encountered due endemic pests and diseases as well as quality of seed. Besides, post-harvest handling is also less of a concern because it is still traditional. Thus there are still opportunities to be able to increase the production of shallot by improving seed genetic resources and farming technologies. Government support is needed for the provision of warehouse facilities in strategic markets and improved transportation facilities to maintain the quality.